Combination therapy with Nifuroxazide and Lenvatinib exerts superior anti-hepatocellular carcinoma effect by enhancing the anti-tumor immune response - Jing Yang; Jiaxin Geng; Yue Yin; Kangle Wang; Leyao Tian; Jingyi Wang; Huijie Jia; Lei Wang; Yongxi Zhang; Tiesuo Zhao (Frontiers in Oncology, 2026)
Background Lenvatinib is a first-line multi-target tyrosine kinase inhibitor for hepatocellular carcinoma (HCC) that exerts anti-angiogenic effects by blocking VEGF signaling. However, its clinical efficacy is often compromised by adaptive resistance. Nifuroxazide, an anti-diarrheal agent, has been identified by our group as a potent inhibitor of PD-L1 expression in HCC. Objective This study aimed to evaluate the therapeutic potential and underlying molecular mechanisms of nifuroxazide combined with lenvatinib against HCC. Methods In vitro , HCC cell proliferation, colony formation, and migration were assessed, and Western blot was used to detect p-STAT3, STAT3, PD-L1, and VEGF levels. In vivo , antitumor efficacy was evaluated in mouse xenograft models. Tumor tissues were analyzed by immunohistochemistry, TUNEL, and H&E staining, while flow cytometry was used to measure CD4 + and CD8 + T-cell proportions in the tumor microenvironment, peripheral blood, and spleen. Results The combination synergistically inhibited HCC cell proliferation and migration, and downregulated PD-L1, p-STAT3, and VEGF expression. It also markedly suppressed tumor growth, induced apoptosis, and enhanced CD4 + and CD8 + T-cell infiltration and distribution. Conclusions Nifuroxazide potentiates lenvatinib-induced antitumor activity by regulating the STAT3/PD-L1 axis and enhancing antitumor immune responses. This combination provides a promising therapeutic strategy for HCC.